Aging and perceptual-motor expertise in handball goalkeepers - Schorer, J.; Baker, J. (Experimental Aging Research, 2009)
Few studies have examined the effect of age on skilled perception. The purpose of this study was to determine whether the perceptual-motor abilities of highly skilled performers in dynamic, time-constrained sports exhibited the same pattern of age-related decline seen in other areas. The sample for this study involved five age-specific groups of handball goalkeepers. Each participant completed an eye-tracking task, a temporal occlusion task, and an eight-choice reaction time task. Results revealed age-related declines in motor performance but not perceptual performance. Skilled perception appears resistant to normal age normal age-related declines over time through the use of compensatory mechanisms.